The Development of Teacher’s Professional Competence: A Theoretical Review - Rahmah, Syarifah; Kadi, Titi (Idarah (Jurnal Pendidikan dan Kependidikan), 2022)
The functionalization of teachers as the primary contributor to educational quality is demonstrated by their mastery of professional facets. The purpose of this study is to design and examine a model for teacher professional development. a qualitative study design using literary methods. Using the keywords "teacher competence," "teacher professionalism," "professional development," and "educational management," 45 data sources were extracted from main and secondary references in the form of books, research journals, and documentation. Coding, keywords, and classification are then used to process the data. Miles and Huberman's procedures are employed in data analysis. The findings demonstrated that teachers' professional orientation does not end at the point of demonstrating competence but rather develops unique teacher-learner relations. Both internal and external factors have an impact on the professional development of teachers. Internal competence development entails taking several calculated actions. The professional development of teachers is an endeavor to reenergize instructors that are carried out outside of classrooms. Observations of the teaching profession are generally becoming more forward-looking. The idealization is consistent with the official government policies.